Identification and Characterization of Phytochemicals in Avocado (Persea americana Mill, var. Hass) Fruit at Different Maturation and Ripening Stages - Elhadi M. Yahia; Gustavo Adolfo González-Aguilar; José de Jesús Ornelas-Paz; Ivan Luzardo-Ocampo (Journal of Food Quality)
Avocado (Persea americana Mill.) is currently among the most demanded fruit crops worldwide due to its nutritional and health benefits. Despite the abundance of reports that have chemically and nutritionally characterized the fruit, information about the characterization of the fruit’s phytochemicals at specific maturation and ripening stages is still scarce. This research was aimed to identify and quantify several phytochemicals in ‘Hass’ avocado fruit at different maturation and ripening stages considering their dry matter values (∼20% to over 38%), corresponding to 10.99% and 26.23% oil content, as objective and quantitative parameters of avocado maturation and ripening. Palmitic (1.54–4.46 g/100 g), palmitoleic (0.88–2.60 g/10 0g), and linoleic (0.39–0.93 g/100 g) acids were the dominant fatty acids, showing a decreasing trend during ripening compared to the initiation of maturation (20% DM). β-sitosterol did not change during maturation and ripening, but ergosterol and brassicasterol disappeared at the end of ripening (38.8% DM). β-carotene was maintained at low concentrations (0.04–0.12 mg/100 g) during maturation and ripening, and lutein reached the highest concentration (6.89 mg/100 g) of all the carotenoids at 32.56% DM. α-Tocopherol increased during ripening (up to 0.35 mg/100 g), particularly at 35% DM. Among the phenolic compounds, gallic acid, catechin, chlorogenic acid, and vanillic acid reached their peak concentration (0.32–2.01 mg/100 g) between 33.84% and 36.99% DM. ‘Hass’ avocados contain significant quantities of bioactive compounds that are of great benefit to human nutrition and health, but their presence and evolution should be well correlated with properly established maturation and ripening stages.